2012
DOI: 10.1029/2012wr011877
|View full text |Cite
|
Sign up to set email alerts
|

The impact of wettability and connectivity on relative permeability in carbonates: A pore network modeling analysis

Abstract: [1] We use pore network modeling to study the impact of wettability and connectivity on waterflood relative permeability for a set of six carbonate samples. Four quarry samples are studied, Indiana, Portland, Guiting, and Mount Gambier, along with two subsurface samples obtained from a deep saline Middle Eastern aquifer. The pore space is imaged in three dimensions using X-ray microtomography at a resolution of a few microns. The images are segmented into pore and solid, and a topologically representative netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 32 publications
10
54
1
Order By: Relevance
“…The precise explanation for the discrepancy between the provider's and our porosity measurements is unclear, and may be due to differences in the methodologies performed. However, the porosity found in this study matched closely with that reported by other researchers, 11% [41] and 13.05% [40].…”
Section: Porositysupporting
confidence: 82%
See 4 more Smart Citations
“…The precise explanation for the discrepancy between the provider's and our porosity measurements is unclear, and may be due to differences in the methodologies performed. However, the porosity found in this study matched closely with that reported by other researchers, 11% [41] and 13.05% [40].…”
Section: Porositysupporting
confidence: 82%
“…distributed throughout the material. This qualitative evaluation of Indiana Limestone is consistent with previous studies of this rock [40]. As stated above, this work represents the first micro-structural evaluation of Pink Dolomite.…”
Section: Invasion Percolationsupporting
confidence: 77%
See 3 more Smart Citations